Identifizierung des Zustandsparameters für viskoelastiche Materialien (II): Identification of the state parameter for viscoelastic materials (II) - Buggisch, H.; Mazilu, P.; Weber, H. (Rev. Anal. Numér. Théor. Approx., 1994)
Not available.